Field ionization detection of helium using a planar array of carbon nanotubes - O’Donnell, Kane; Fahy, A.; Barr, M.; Allison, W.; Dastoor, P. (American Physical Society, 2012)
In this work we demonstrate the field ionization of neutral helium using a carbon nanotube forest in a parallel-plate detector geometry. The nanotube forest was grown using plasma-enhanced chemical vapor deposition on a silicon substrate. With a high positive voltage applied to the nanotubes, the measured ion current was directly correlated with the helium partial pressure. Moreover, we show that multiple nanotubes act as field ionisation sources suggesting that, with careful nanotube engineering, significantly larger numbers of nanotubes should be able to contribute to the measured current, paving the way for high-efficiency, spatially resolved field ionization detection.